2014
DOI: 10.3390/su6063338
|View full text |Cite
|
Sign up to set email alerts
|

Can Companies Induce Sustainable Consumption? The Impact of Knowledge and Social Embeddedness on Airline Sustainability Programs in the U.S.

Abstract: This paper investigates how consumers' level of knowledge and social embeddedness can influence sustainable consumption. An extended model of goal-directed behavior (MGB) is tested by U.S. airline consumers who have participated in UNICEF's Change for Good (CFG) and voluntary carbon offsetting (VCO) programs. Results show that consumers' knowledge positively influenced their subjective norms and attitudes towards participation of VCO and CFG. Increasing consumers' sense of social embeddedness is also found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 50 publications
4
45
0
Order By: Relevance
“…Sustainability 2017, 9, 77 9 of 14 drive farmers to adopt water saving measures, the present study embraced the well-known Ajzen's Theory of Planned Behavior [11], which in spite of its extensive use in the literature on proenvironmental behaviors (e.g., [71][72][73]), has rarely been employed to investigate the determinants of farmers' intentions to adopt water saving measures. Consistent with previous research [29], this study established that farmers' favorable attitudes toward water saving measures predict their intention to adopt them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability 2017, 9, 77 9 of 14 drive farmers to adopt water saving measures, the present study embraced the well-known Ajzen's Theory of Planned Behavior [11], which in spite of its extensive use in the literature on proenvironmental behaviors (e.g., [71][72][73]), has rarely been employed to investigate the determinants of farmers' intentions to adopt water saving measures. Consistent with previous research [29], this study established that farmers' favorable attitudes toward water saving measures predict their intention to adopt them.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the motivational factors that could drive farmers to adopt water saving measures, the present study embraced the well-known Ajzen's Theory of Planned Behavior [11], which in spite of its extensive use in the literature on pro-environmental behaviors (e.g., [71][72][73]), has rarely been employed to investigate the determinants of farmers' intentions to adopt water saving measures.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kim et al [103], knowledge will also increase the belief that one has control of the situation, thereby increasing perceived behavioral control. Therefore, it is hypothesized that: H11: Environmental knowledge is positively associated with perceived behavioral control.…”
Section: Environmental Knowledge (Ek)mentioning
confidence: 99%
“…The study by Van Birgelen et al (2011) indicated that there was a significantly positive correlation between a high school teacher's environmental sensitivity and the environmental knowledge. For the correlation between perception and the affective domain, Kim et al (2014) proposed that an elementary school teacher's environmental knowledge was positively correlated to the perception of environmental problems in Taiwan, environmental awareness, cosmic belief, and social values. Araghi et al (2014) selected students of a public vocational training organization as the research targets and discovered that there was a significant correlation between a student's environmental knowledge and his/her environmental attitude.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Any knowledge relevant to this territory was included in the scope of the environmental knowledge. Kim et al (2014) proposed eleven principal ideas of the teaching materials for environmental education, including the general concepts, air pollution, noise pollution, urban problem, balance of nature, forest and wood preservation, human resource preservation, land resource maintenance, wise utilization of minerals, hydraulic resource preservation, and wildlife preservation. Araghi et al (2014) proposed that the environmental knowledge was an interdisciplinary subject that was a type of knowledge derived from the nature, social science, and anthropology.…”
Section: Environmental Knowledgementioning
confidence: 99%